PKM KELOMPOK TANI DALAM PRODUKSI, MANAJEMEN USAHA DAN PEMASARAN PUPUK ORGANIK CAIR, KOMPOS DAN PERSTISIDA NABATI DAUN PAITAN (Tithonia diversifolia) DI DESA KARANG JAYA KECAMATAN SELUPU REJANG - Ria Dwi Jayati; Nur Fitriyana; Lucy Asri Purwasi (LP4MK STKIP PGRI Lubuklinggau, 2019)
The Community Partnership Program that we propose is expected to help communities and farmer groups in Karang Jaya Village in the production, business management and marketing of liquid organic fertilizer, compost and paitan leaf organic pesticides (Tithonia diversifolia). To create business opportunities, training and assistance is given to farmer groups in production, business management and marketing of liquid organic fertilizers, organic pesticides and paitan leaf compost. The activities that we undertake to achieve these objectives are by using methods of observation, socialization, training and continued with direct practice and assistance in production, business management and product marketing. The results of the Community Partnership Program that have been implemented are partners having knowledge about the dangers of using chemical fertilizers and chemical pesticides for health and the environment, knowing the business opportunities of paitan plants by processing them into liquid organic fertilizer, organic pesticides and compost. Partners also have the knowledge and skills in creating, packaging, marketing and managing business products that are produced. Availability of supporting tools that will facilitate partners in producing liquid organic fertilizer, organic pesticides and compost.